2013
DOI: 10.1093/nar/gkt647
|View full text |Cite
|
Sign up to set email alerts
|

Global identification of conserved post-transcriptional regulatory programs in trypanosomatids

Abstract: While regulatory programs are extensively studied at the level of transcription, elements that are involved in regulation of post-transcriptional processes are largely unknown, and methods for systematic identification of these elements are in early stages. Here, using a novel computational framework, we have integrated sequence information with several functional genomics data sets to characterize conserved regulatory programs of trypanosomatids, a group of eukaryotes that almost entirely rely on post-transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
(40 reference statements)
0
38
0
1
Order By: Relevance
“…The 25 canonical RBPs include PUF, RRM, CCCH and PSP1 domain‐containing proteins. Two canonical RBPs previously shown to negatively affect gene expression, RBP10 (Wurst et al ., ) and DRBD12 (Najafabadi et al ., ) are in this list. Not surprisingly, five subunits of the CAF1/NOT deadenylase complex reproducibly suppressed PGKB expression suggesting these subunits recruit the unique catalytic subunit CAF1 to the associated reporter mRNA (Farber et al ., ; Erben et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The 25 canonical RBPs include PUF, RRM, CCCH and PSP1 domain‐containing proteins. Two canonical RBPs previously shown to negatively affect gene expression, RBP10 (Wurst et al ., ) and DRBD12 (Najafabadi et al ., ) are in this list. Not surprisingly, five subunits of the CAF1/NOT deadenylase complex reproducibly suppressed PGKB expression suggesting these subunits recruit the unique catalytic subunit CAF1 to the associated reporter mRNA (Farber et al ., ; Erben et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Culturing and transfection of trypanosomes (Lister 427 strain expressing the tetracycline (tet) repressor from pHD1313 and 29–13) were performed as described in [20].…”
Section: Methodsmentioning
confidence: 99%
“…The metacyclic cells produced in vitro by inducible RBP6 expression were shown to express the VSG coat and importantly, the activated VSG genes possessed a metacyclic‐type VSG Pol I promoter and were found in monocistronic transcription units (Kolev et al ., ). More recently, it was suggested that RBP6 is a remote ELAV‐like T. brucei homologue that binds in vitro to an AU‐rich element (AUUUAUU) present in the 3′UTRs of mRNAs (Najafabadi et al ., ). Interestingly, expression of RBP6 in procyclic cells was found to downregulate mRNAs containing the identified sequence signature mRNAs (Najafabadi et al ., ), an opposite effect in comparison to available data for ELAV family proteins from other species.…”
Section: Rbps During Trypanosome Development In the Tsetse Flymentioning
confidence: 97%
“…More recently, it was suggested that RBP6 is a remote ELAV‐like T. brucei homologue that binds in vitro to an AU‐rich element (AUUUAUU) present in the 3′UTRs of mRNAs (Najafabadi et al ., ). Interestingly, expression of RBP6 in procyclic cells was found to downregulate mRNAs containing the identified sequence signature mRNAs (Najafabadi et al ., ), an opposite effect in comparison to available data for ELAV family proteins from other species. Identifying the precise in vivo RNA binding sites for RBP6 will undoubtedly clarify the repertoire of RBP6 targets and shed more light on its mode of action.…”
Section: Rbps During Trypanosome Development In the Tsetse Flymentioning
confidence: 97%